Recognize Geometry Shapes through Computer Learning in Early Math Skills - Putri, Ayu Aprilia; Suparno (Jurnal Pendidikan Usia Dini, 2020)
One form of early mathematical recognition is to introduce the concept of geometric shapes. Geometry is an important scientific discipline for present and future life by developing various ways that fit 21st century skills. This study aims to overcome the problem of early mathematical recognition of early childhood on geometry, especially how to recognize geometric forms based on computer learning. A total of 24 children aged 4-5 years in kindergarten has to carrying out 2 research cycles with a total of 5 meetings. Treatment activities in each learning cycle include mentioning, grouping and imitating geometric shapes. There were only 7 children who were able to recognize the geometric shapes in the pre-research cycle (29.2%). An increase in the number of children who are able to do activities well in each research cycle includes: 1) The activities mentioned in the first cycle and 75% in the second cycle; 2) Classifying activities in the first cycle were 37.5% and 75% in the second cycle; 3) Imitation activities in the first cycle 54.2% and 79.2% in the second cycle. The results of data acquisition show that computer learning application can improve the ability to recognize geometric shapes, this is because computer learning provides software that has activities to recognize geometric shapes with the animation and visuals displayed. Keywords: Early Childhood Computer Learning, Geometry Forms, Early Math Skills Reference Alia, T., & Irwansyah. (2018). Pendampingan Orang Tua pada Anak Usia Dini dalam Penggunaan Teknologi Digital. A Journal of Language, Literature, Culture and Education, 14(1), 65– 78. https://doi.org/10.19166/pji.v14i1.639 Ameliola, S., & Nugraha, H. D. (2013). Perkembangan Media Informasi dan Teknologi Terhadap Anak di Era Globalisasi. International Conferences in Indonesian Studies : “Etnicity and Globalization.” Anderson, L. W., Krathwohl, D. R., & Bloom, B. S. (2001). A taxonomy for learning, teaching, and assessing: a revision of Bloom’s taxonomy of educational objectives. New York: Longman. Arikunto, S. (2010). Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta: Asdi Mahasatya. Arsyad, N., Rahman, A., & Ahmar, A. S. (2017). Developing a self-learning model based on open-ended questions to increase the students’ creativity in calculus. Global Journal of Engineering Education, 19(2), 143–147. https://doi.org/10.26858/gjeev19i2y2017p143147 Asiye, I., Ahmet, E., & Abdullah, A. (2018). Developing a Test for Geometry and Spatial Perceptions of 5-6 Year-Old. Kastamonu Education Journal, 26(1). Aslan, D., & Yasare, A. (2007). Three to Six Years OldChildren’s Recognition of Geometric Shapes. International Journal of Early Years Education, 15 :1, 83–104. Ben-Yehoshua, D., Yaski, O., & Eilam, D. (2011). Spatial behavior: the impact of global and local geometry. Animal Cognition Journal, 13(3), 341–350. https://doi.org/10.1007/s10071- 010-0368-z Charlesworth, R., & Lind, K. K. (2010). Math and Sciend for Young Children. Canada: Wadsworth/Cengage Learning. Chen, J.-Q., & Chang, C. (2006). using computers in early childhood classrooms teachers’ attitudes,skills and practices. Early Childhood Research. Clements, D. H., & Samara. (2003). Strip mining for gold: Research and policy in educational technology—a response to “Fool’s Gold.” Association for the Advancement of Computing in Education (AACE) Journal, 11(1), 7–69. Cohen, L., & Manion, L. (1994). Research Methods in Education (fourth edi). London: Routledge. Conorldi, C., Mammarela, I. C., & Fine, G. G. (2016). Nonverbal Learning Disability (J. P. Guilford, Ed.). New York. Corey, S. M. (1953). Action Research to Improve School Practice. New York: Teachers College, Columbia University. Couse, L. J., & Chen, D. W. (2010). A tablet computer for young children? Exploring its viability for early childhood education. Journal of Research on Technology in Education, 43(1), 75– 98. https://doi.org/10.1080/15391523.2010.10782562 Delima, R., Arianti, N. K., & Pramudyawardani, B. (2015). Identifikasi Kebutuhan Pengguna Untuk Aplikasi Permainan Edukasi Bagi Anak Usia 4 sampai 6 Tahun. Jurnal Teknik Informatika Dan Sistem Informasi, 1(1). Depdiknas. (2007). Permainan Berhitung Permulaan Di Taman Kanak-kanak. In Pedoman Pembelajaran. Jakarta: Depdiknas. Djadir, Minggi, I., Ja’faruddin., Zaki, A., & Sidjara, S. (2017). Sumber Belajar PLPG 2017: Bangun Datar. In Modul PLPG. Jakarta: Kementrian Pendidikan dan Kebudayaan Direktorat Jenderal Guru dan Tenaga Kependidikan.Dooley, T., Dunphy, E., & Shiel, G. (2014). Mathematics in Early Childhood and Primary Education (3-8 years). Duncan, G. J., Dowsett, C. J., Claessens, A., Magnuson, K., Huston, A. C., Klebanov, P., ... Japel, C. (2007). School Readiness and Later Achievement. Developmental Psychology, 43(6), 1428–1446. https://doi.org/10.1037/0012-1649.43.6.1428 Duncan, G. J., & Magnuson, K. (2011). The nature and impact of early achievement skills, attention skills, and behavior problems. Whither Opportunity?: Rising Inequality, Schools, and Children’s Life Chances, (0322356), 47–69. Edwards, S. (2009). Early Childhood Education and Care: a sociocultural Approach. New South Wales: Pademelon Press. Feliyanah, Norman, S., & Yulidesni. (2014). Meningkatkan Kemampuan Matematika dengan Menggunakan Teknik Mengurutkan dan Membandingkan. Universitas Bengkulu. Gardner, H. (2011). Frame of Mind ; The theory of Multiple Intelegences. New York: Basic Book. Gimbert, B., & Cristol, D. (2004). Teaching Curriculum with Technology: Enhancing Children’s Technological Competence During Early Childhood. Early Childhood Education Journal, 31(1). Gulay, H. (2011a). The evaluation of the relationship between the computer using habits and proso_cial and aggressive behaviours of 5–6 years old children. International Journal of Academic Research, 3(2), 252. Gulay, H. (2011b). The evaluation of the relationship between the computer using habits and proso_cial and aggressive behaviours of 5–6 years old children. International Journal of Academic Research, 3(2), 252–257. Gunawan, I., & Palupi, A. R. (2012). Taksonomi Bloom-Revisi Ranah Kognitif; Kerangka Landasan untuk Pembelajaran, Pengajaran, dan Penilaian. Jurnal Pendidikan Dasar Dan Pembelajaran, 2 No.2, 100–108. Inan, H. Z., & Dogan-Temur, O. (2010). Understanding kindergarten teachers’ perspectives of teaching basic geometric shapes: A phenomenographic research. ZDM - International Journal on Mathematics Education, 42(5), 457–468. https://doi.org/10.1007/s11858-010- 0241-1 Jackman, H. I., Beaver, N. H., & Wyatt, S. S. (2014). Early Childhood Curriculum: A child’s connection to the world. (sixth edit). Canada: Cengage Learning. Kennedy, L. M., Tipps, S., & Johnson, A. (2008). Guiding Children’s Learning of Mathematic (Eleventh E; Belmot, Ed.). CA: Thomson Wadsworth. Mackintosh, B. B., & McCoy, D. C. (2019). Exploring Social Competence as a Mediator of Head Start’s Impact on Children’s Early Math Skills: Evidence from the Head Start Impact Study. Early Education and Development, 30(5), 655–677. https://doi.org/10.1080/10409289.2019.1576156 Martin, M. O., Mullis, I. V. S., Foy, P., & Stanco, G. M. (2011). Results in Science. Mirawati. (2017). Matematika Kreatif; Pembelajaran Matematika bagi Anak Usia Dini Melalui Kegiatan yang Menyenangkan dan Bermakna. Jurnal Anak Usia Dini Dan Pendidikan Anak Usia Dini, 3. Mohammad, M., & Mohammad, H. (2012). Computer integration into the early childhood curriculum. Education, 133(1), 97–116. National Research Council. (2009). Mathematics Learning in Early Chidhood Paths Toward Excellence and Equity (C. T. Cross, T. Woods, & H. Schweingruber, Eds.). Washinton D.C: The National Academies Press. Norton, A., & Nurnberger-Haag, J. (2018). Bridging frameworks for understanding numerical cognition. Journal of Numerical Cognition, 4(1), 1–8. https://doi.org/10.5964/jnc.v4i1.160 Novitasari, D. R. (2010). Pembangunan Media Pembelajaran Bahasa Inggris Untuk Siswa Kelas 1 Pada Sekolah Dasar Negeri 15 Sragen. Sentra Penelitian Engineering Dan Edukas, Volume 2 N. Papadakis, S., Kalogiannakis, M., & Zaranis, N. (2017). Improving Mathematics Teaching in Kindergarten with Realistic Mathematical Education. Early Childhood Education Journal, 45(3), 369–378. https://doi.org/10.1007/s10643-015-0768-4 Papalia, Old, & Feldman. (2009). Human Development (Psikologi Perkembangan (Kesembilan). Jakarta: Kencana. Paquette, K. R., Fello, S. E., & Jalongo, M. R. (2007). The talking drawings strategy: Using primary children’s Illustrations and oral language to improve comprehension of expository text. Early Childhood Education Journal, 35(1), 65–73. https://doi.org/10.1007/s10643- 007-0184-5 Putra, L. D., & Ishartiwi. (2015). Pengembangan Multimedia Pembelajaram Interaktif Mengenal Angka dan Huruf untuk Anak Usia Dini. Jurnal Inovasi Teknologi Pendidikan, 2(2). Rich, B., & Thomas, C. (2009). Geometry: Includes Plane, Analytic, and Transformational Geometries. . (4th Editio). New York: McGraw-Hill. Rochanah, L. (2016). Pemanfaatan Media Berbasis Komputer Untuk Meningkatkan Kemampuan Huruf pada Anak Usia Dini (Urgensi Media Berbasis Komputer pada Peningkatan Kemampuan Mengenal Huruf ). Jurnal Program Studi PGRA, Volume 2 N, 1–8. Runtukahu, T., & Kandou, S. (2014). Pembelajaran matematika dasar bagi anak berkesulitan belajar. Yogyakarta: Ar-ruzz Media. Santrock, J. W. (2016). Children (Thirteenth). New York: McGraw-Hill Education. Sarama, J., & Clements, D. H. (2006). Mathematics, Young Students, and Computers: Software, Teaching Strategies and Professional Development. The Mathematics Educato, 9(2), 112– 134. Schoenfeld, A. H., & Stipek, D. (2011). Math Matters. Barkeley, California.Shilpa, S., & Sunita, M. (2013). A Study About Role of Multimedia in Early Childhood Education. International Journal of Humanities and Social Science Invention, 2(6). Siswono, T. Y. E. (2012). Belajar dan Mengajar Matematika Anak Usia Dini. Universitas Negeri Surabaya.Smaldino, S. E., Russel, J. D., & Lowther, D. L. (2014). Instructional Technology & Media for Learning (9th ed.). Jakarta: Kencana Prenada Media Group. Sudaryanti. (2006). Pengenalan Matematika Anak Usia Dini. Yogyakarta: FIP UNY. Sufa, F. F., & Setiawan, H. Y. (2017). Analisis Kebutuhan Anak Usia 4-6 Tahun Pada Pembelajaran Berbasis Komputer Pada Anak Usia Dini. Research Fair Unisri, 1(1). Suharjana, A. (2008). Pengenalan Bangun Ruang dan Sifat-sifatnya di SD. Yogyakarta: Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika. Sujiono, Y . N. (2014). Batasan dan Dasar T eori Pengembangan Kognitif. In Hakikat Pengembangan Kognitif (p. 12). Suryana, D. (2013). Pendidikan Anak Usia Dini (teori dan praktik pembelajaran). Padang: UNP Press. Susperreguy, M. I., & Davis-Kean, P. E. (2016). Maternal Math Talk in the Home and Math Skills in Preschool Children. Early Education and Development, 27(6), 841–857. https://doi.org/10.1080/10409289.2016.1148480 Suwarna. (2010). Pengembangan Multimedia Pembelajaran untuk Pembinaan Kreativitas Melukis di Taman Kanak-kanak. Jurnal Universitas Negeri Yogyakarta. Suziedelyte, A. (2012). Can video games affect children’s cognitive and non-cognitive skills? UNSW Australian School of Business Research Paper. https://doi.org/10.2139/ssrn.2140983 Tarigan, D. (2006). Pembelajaran Matematika Realistik. Jakarta: Departeman Pendidikan Nasional, Direktorat Jendral Pendidikan Tunggi, Direktorat Pembinaan Pendidikan Tenaga Kependidikan dan Ketenaga Perguruan Tinggi. Tatang, S. (2012). Ilmu Pendidikan. Bandung: Pustaka Setia.Trawick, M. (2007). Enemy Line ; Warfare, Childhood, and Play in Batticaloa. London: University of California Press. Trifunović, A., Čičević, S., Lazarević, D., Mitrović1, S., & Dragovi, M. (2018). Comparing Tablets (Touchscreen Devices and PCs in Preschool Children Education: Testing Spatial Relationship Using Geometric Syimbols Traffic Signs. IETI Transections on Economics and Safety, 2(1), 35–41. https://doi.org/10.6722/TES.201808_2(1).0004 Vitianingsih, A. V. (2016). Game Edukasi Sebagai Media Pembelajaran Pendidikan Anak Usia Dini. Jurnal INFORM, 1 No. 1. Wang, F., & Kinzie, M. B. (2010). Applying Technology to Inquiry- Based Learning in Early Childhood Education. Early Childhood Education Journal. Weil, M., Calhoun, E., & Joyce, B. (2011). Models of Teaching. New York.: New York. Zack, N. (2014). Philosophy of Science and Race. New York: Routledge. Zare, Sarikhani, Salarii, & Mansouri. (2016). The Impact Of E-learning on University Student’s Academic Achievement and Creativity. Journal of Technical Education and Training (JTET), 8(11).